Revision of Malagasy Odontepyris Kieffer (Hymenoptera, Bethylidae) - Alencar, Isabel D. C. C.; Azevedo, Celso O. (Zootaxa, 2011)
Four new species of Odontepyris from Madagascar are described and illustrated: O. acrius Alencar et Azevedo, sp. nov., O. cynpus Alencar et Azevedo, sp. nov., and O. escus Alencar et Azevedo, sp. nov. based on females and O. bedus Alencar et Azevedo, sp. nov. based on both males and females. Placoid sensillae in medial surface of flagellomere is firstly recorded to Bethylidae. A key to Malagasy species is provided.